Effectiveness and safety of tenofovir amibufenamide and tenofovir alafenamide in treating elderly patients diagnosed with decompensated hepatitis B cirrhosis: a retrospective cohort study - Qiu, Xinye; Yin, Yue; Zhang, Shibin; Liu, Wei (Frontiers in Pharmacology, 2025)
Background/aimTenofovir amibufenamide (TMF) has demonstrated significant antiviral activity and safety in individuals with chronic hepatitis B (CHB) in randomized clinical trials. The purpose of this study was to investigate the effectiveness and safety disparities between TMF and Tenofovir alafenamide (TAF) in treating elderly patients with decompensated hepatitis B cirrhosis in real-world settings.MethodsA retrospective cohort analysis of elderly patients with decompensated hepatitis B cirrhosis who were treated with TMF or TAF in our hospital’s outpatient department between January 2022 and December 2023 was the focus of this study. Following a 24-week treatment period, this study evaluated the disparities between the TMF and TAF groups in terms of primary efficacy endpoints (virologic response rate, VR rate), secondary efficacy endpoints (normalization rate of ALT, HBsAg and HBeAg clearance rate, HBsAg and HBeAg seroconversion rates), as well as safety endpoints related to renal function and blood lipids.ResultsThe study included 171 patients (93 in the experimental group and 78 in the control group). Following a 24-week treatment period, HBV DNA, HBsAg, ALT, AST, and TBIL had significantly decreased compared to the baseline level, and the differences were statistically difference. Cr, eGFR, triglyceride, and TG had no significant changes compared with the baseline level, and the differences were no statistical difference. The virologic response rate in the experimental group was 70.97% (33/93), and that in the control group was 73.08% (57/78), with no statistical difference observed between the two groups (P = 0.760). ALT normalization rate was 83.33% in the experimental group and that was 100% in the control group, and there was not a statistically significant distinction between the two groups (P = 0.229). Compared with baseline data, Cr and eGFR of the experimental group increased (2.97 ± 14.66 μmol/L, P = 0.867; 0.29 ± 6.76 mL/min/1.72 m2, P = 0.680), TC and TG decreased (−0.5 ± 1.30 mmol/L, P = 0.589; −0.006 ± 0.23 mmol/L, P = 0.986), however, no statistical difference was observed. Compared with the control group, the change of safety dates was also no statistical difference.ConclusionTMF treatment in elderly patients with decompensated hepatitis B cirrhosis had a good antiviral effect, no adverse drug reaction on renal function and blood lipids, and high safety. TMF is not inferior to TAF in antiviral efficacy and safety.